ANALISIS KOMUNIKASI PADA PROGRAM PEMBERDAYAAN MASYARAKAT (STUDI KASUS PROGRAM CORPORATE SOCIAL RESPONSIBILITY PENDIDIKAN PT. ADARO INDONESIA) - Dedi Setia Rahman; Harunnurrasyid Harunnurrasyid; Sanusi Sanusi (Al-KALAM : JURNAL KOMUNIKASI, BISNIS DAN MANAJEMEN, 2018)
The purpose of this study was to determine how Communication Analysis Community Empowerment Program (A Case Study Corporate Social Responsibility Education Program). The method used in this study is a qualitative research method, this method is trying to describe and explain an event by looking at the facts that exist as observations, but researcher also analyze and integrate, after that researcher conducted a classification. Data collection methods that writer use are interviews and documentaries.These results indicate CSR Department PT. Adaro Indonesia also implements its management as POAC (Planning, Organizing, Actuating, Controlling). Fund management process of Adaro's CSR program PT. Adaro Indonesia is closely related to the district government. The results of the research, it was found that the knowledge of the community has a moderate level of knowledge on CSR.